Modelling general dependence between commodity forward curves - Mikhail Zolotko; Ostap Okhrin (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
This study proposes a novel framework for the joint modelling of commodity forward curves. Its key contribution is twofold. First, dynamic correlation models are applied in this context as part of the modelling scheme. Second, we introduce a family of dynamic conditional correlation models based on hierarchical Archimedean copulae (HAC DCC), which are flexible, but parsimonious instruments that capture a wide range of dynamic dependencies. The conducted analysis allows us to obtain precise out-of-sample forecasts of the distribution of the returns of various commodity futures portfolios. The Value-at-Risk analysis shows that HAC DCC models outperform other introduced benchmark models on a consistent basis.
Keywords: C13; C53; Q40; 330; commodity forward curves; multivariate GARCH; hierarchical Archimedean copula; Value-at-Risk; Rohstoffderivat; Börsenkurs; ARCH-Modell; Multivariate Analyse; Kopula (Mathematik); Risikomaß; Theorie